3-Monochloropropane-1, 2-diol (alpha-chlorohydrin) disrupts spermatogenesis and causes spermatotoxicity in males of the Egyptian fruit-bat (Rousettus aegyptiacus). (19th May 2018) - Mahmoud, YI; Taha, A; Soliman, S
Abstract: We evaluated the sterilizing effect of 3-monochloropropane-1, 2-diol (3-MCPD) in male Egyptian fruit bats ( Rousettus aegyptiacus ). We used three groups. One was treated with 70 mg/kg 3-MCPD for 4 days. The second group was treated with 3-MCPD as a bait formulation (known concentration of 3-MCPD mixed with a known amount of food). The third group was untreated controls. We compared the weights of the reproductive organs, histology of the testes, occurrence of spermatogenesis, and the count, motility and abnormalities of epididymal sperm of treated males with those of the untreated control group. 3-MCPD caused significantly decreased weights of reproductive organs, several testicular histological alterations and spermatogenic arrest accompanied by significant decreases in sperm count and motility, and significantly increased number of abnormal sperm. 3-MCPD bait was readily accepted by the animals. 3-MCPD, even in low doses and after limited exposure, disrupted spermatogenesis in males of the Egyptian fruit bat. Our findings have potential value for public health and agricultural authorities, and for vertebrate pest managers. 3-MCPD may have application for control of this pest.